Risk and Return Analysis of Government Bonds in Indonesia: A Multifactor Model Approach - Siti Amaliah; Isni Andriana; Muizzudin Muizzudin (Iranian Journal of Accounting, Auditing & Finance)
Understanding the relationship between risk and government bond returns is crucial for assessing the influence of risk factors on bond returns. This study investigates the dynamics of risk-taking behavior and its impact on the performance of government bonds in Indonesia. Using monthly data spanning from January 2017 to December 2021, we employ a multifactor model with GARCH analysis technique to analyze the data. The findings reveal that risk exposure exerts a negative and significant effect on government bond returns in Indonesia, while market factors also negatively and significantly influence bond returns. Conversely, the joint stock performance exhibits a positive relationship and significantly impacts returns in Indonesia.